2018
DOI: 10.1111/jpc.14063
|View full text |Cite
|
Sign up to set email alerts
|

Parental experiences of family‐centred care from admission to discharge in the neonatal intensive care unit

Abstract: The challenges relating to FCC reported by parents at both admission and discharge represent some of the key barriers that parents still face in terms of being truly involved in the care of their infant in the NICU. Similar themes at both time points suggest that parents need equal amounts of support during their stay in NICU, irrespective of the level of care the infant is receiving and whether they are approaching discharge. Implications for improving FCC more generally are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 33 publications
1
58
0
7
Order By: Relevance
“…The intervention created mutual partnership between the staff and parents, which has been difficult to establish in many units. 8,10 The first step in this process was to remove limitations concerning parental presence so that the parents could participate in all aspects of care. Shared caregiving practiced during the intervention helped the staff to support and trust the parents' ability to take care of their infant.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The intervention created mutual partnership between the staff and parents, which has been difficult to establish in many units. 8,10 The first step in this process was to remove limitations concerning parental presence so that the parents could participate in all aspects of care. Shared caregiving practiced during the intervention helped the staff to support and trust the parents' ability to take care of their infant.…”
Section: Discussionmentioning
confidence: 99%
“…The staff learned to give more space for parents to express themselves, which was indicated by an increased total score of the category "Empowered decision making". Previous studies have reported mothers' feelings of being a visitor 10 and not being a part of the team 19 when they are not provided the opportunity to participate in medical rounds or when doctors did not really listen to them during rounds. In addition, inconsistency in involving parents in decision making has been reported as a challenge for providing FCC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations